Minjingu phosphate rock availability in low-pH highly weathered soil as affected by added salts - Savini, Isaac; Koala, Saidou; Kihara, Job Maguta (FapUNIFESP, 2015)
Concentrations and identity of ions in the soil solution may affect soil phosphorus (P) reactions and P availability. In this study, the magnitude of these reactions was evaluated following the application of Minjingu phosphate rock (MPR) combined with chloride and carbonate salts of Na and Ca within an incubation experiment. Twenty-one days later NaOH-P and HCl-P were determined. This investigation was undertaken with the aim of identifying the role of Ca-ion activity in the liquid phase on the solubilization of MPR and formation of insoluble Ca-P phases. The increase in pH was higher with Na2CO3 than with CaCO3, while both CaCl2 and NaCl resulted in slight decreases in pH. The dissolution of MPR was higher overall when MPR was applied singularly than for the combined application of the phosphate rock with salts of calcium or sodium after 60 days of incubation. Dissolution of MPR decreased as levels of CaCO3 or CaCl2 increased but the decrease was more pronounced in CaCO3-treated than in CaCl2-treated soils. Ca-ion activity in the liquid phase is the main factor responsible for the insolubilization of MPR and the formation of insoluble Ca-P phases (HCl P). The formation of Ca-P solid phases increased with the concentration of Ca-ions, and was governed by the pH and nature of the accompanying anion. For soils with low levels of exchangeable cations and where liming is a recommended intervention measure, Ca from lime will form insoluble P phases and reduce the dissolution of PR and P availability to plants.